Comparative performance of a thermal denuder and a catalytic stripper in sampling laboratory and marine exhaust aerosols. Issue 4 (3rd April 2018) - Amanatidis, Stavros; Ntziachristos, Leonidas; Karjalainen, Panu; Saukko, Erkka; Simonen, Pauli; Kuittinen, Niina; Aakko-Saksa, Päivi; Timonen, Hilkka; Rönkkö, Topi; Keskinen, Jorma
ABSTRACT: The performance of a thermal denuder (thermodenuder—TD) and a fresh catalytic stripper (CS) was assessed by sampling laboratory aerosol, produced by different combinations of sulfuric acid, octacosane, and soot particles, and marine exhaust aerosol produced by a medium-speed marine engine using high sulfur fuels. The intention was to study the efficiency in separating non-volatile particles. No particles could be detected downstream of either device when challenged with neat octacosane particles at high concentration. Both laboratory and marine exhaust aerosol measurements showed that sub-23 nm semi-volatile particles are formed downstream of the thermodenuder when upstream sulfuric acid approached 100 ppbv. Charge measurements revealed that these are formed by re-nucleation rather than incomplete evaporation of upstream aerosol. Sufficient dilution to control upstream sulfates concentration and moderate TD operation temperature (250°C) are both required to eliminate their formation. Use of the CS following an evaporation tube seemed to eliminate the risk for particle re-nucleation, even at a ten-fold higher concentration of semi-volatiles than in case of the TD. Particles detected downstream of the CS due to incomplete evaporation of sulfuric acid and octacosane aerosol, did not exceed 0.01% of upstream concentration. Despite the superior performance of CS in separating non-volatile particles, the TD may still be useful in cases where increased sensitivity over the traditional evaporation tube method is needed and where high sulfur exhaust concentration may fast deplete the catalytic stripper adsorption capacity. Copyright © 2018 American Association for Aerosol Research